POST RENAL TRANSPLANT MALIGNANCIES; A BASIC CONCEPT - Nabi, Zahid; Zahid, Tabeer; Nabi, Rayyan (Journal of Ayub Medical College Abbottabad, 2023)
Background: Kidney transplantation remains the best possible solution for patients with chronic kidney disease, providing better long-term outcomes and drastically improving quality of life. However, it comes with its own set of risks. The use of immunosuppressives following renal transplants has been shown to increase the development of malignancies and infections, and the occurrence of post-transplant malignancies is now the third most common cause of death in transplant patients. This involves multiple mechanisms, including the carcinogenic tendency of some immunosuppressive drugs, along with the induction and promotion of post-transplant malignancies by certain viruses. The quantification of Cancer risk must be made an integral part of the overall management of transplant patients, and appropriate follow-up screening needs to be adopted. Kaposi's sarcoma, lymphoma, and non-melanoma skin cancers have a greater incidence. If a malignancy develops immediately after transplantation, it may have been transmitted from the donor; donor-transmitted and donor-derived tumours may be differentiated based on a two-year time limit. Immunosuppressive medications with carcinogenic tendencies, reduced immunological control of oncogenic viruses, and poor immunosurveillance remain the most important risk factors. The gravity of this situation is further exacerbated by the fact that not only is there an increased risk of developing these malignancies in the post-transplant period, but the prognosis is also worsened when compared to non-transplant patients. All transplant centers should therefore adopt a multidisciplinary approach including early detection and prompt treatment, to improve outcomes in transplanted patients.